Effects of Soil and Water Conservation Practices on Selected Bio-physical, and Livelihood Attributes and Farmer`s Perception at Akusti Micro Watershed, Northwest Ethiopia - Meshesha, Derege Tsegaye; Fisse, Getachew; Ayehu, Rahel (Journal of Agriculture and Environmental Sciences, 2019)
Soil and Water conservation practices are widely practiced in Akusti Micro Watershed (AMW).The main purpose of this study was to assess the effects of soil and water conservation practices (SWCP) on selected biophysical, livelihood attributes and farmer`s perception at AMW, Northwestern Ethiopia. Field survey using questioner was conducted to assess the perceptions of farmers about SWCP. Data was also collected through key informant interviews, focus group discussions, field observations and field measurements and using Google Earth with 30 meter resolution. Data was analyzed using qualitative and quantitative analytical methods using SPSS software. Yield increments were evaluated by using the quadrant measurement 1mÃ—1m (1mÂ²) method. Yields before construction of SWCP were assessed using questioners. The results indicated that about 168.5 hectares of land were covered by vegetation and crop yields were increased, although the increments differed from farmer to farmer as the soil management practices differed. According to the respondents, the productivities of teff, wheat, maize and potato before construction of SWCP were 460 kg/ha, 240 kg/ha, 400kg/ha and 500kg/ha, respectively. After construction of soil and water conservation measures, yields of teff, wheat, maize and potato increased up to 6800, 3500, 12000 and 16000 kg/ha, respectively. According to survey results, 84.2% of the respondents practiced land restoration activities while the remaining 15.8% were not. Farmers who perceived SWCP more effective in controlling soil erosion and ensuring sustainability of crop yields adopted modern conservation methods. In Akusti micro watershed, lands are sloppy and thus soil erosion is very high that removes all the top fertile soils, applied fertilizers and sown seeds. Cultivating these vulnerable lands without proper management may result no or very low harvest. Therefore, it is recommended to integrate the use of agricultural inputs with Swept increase crop yields.